Short and sweet: multiple mini case studies as a form of rigorous case study research - Sebastian Käss; Christoph Brosig; Markus Westner; Susanne Strahringer (Information Systems and e-Business Management, 2024)
Abstract Case study research is one of the most widely used research methods in Information Systems~(IS). In recent years, an increasing number of publications have used case studies with few sources of evidence, such as single interviews per case. While there is much methodological guidance on rigorously conducting multiple case studies, it remains unclear how researchers can achieve an acceptable level of rigour for this emerging type of multiple case study with few sources of evidence, i.e., multiple mini case studies. In this context, we synthesise methodological guidance for multiple case study research from a cross-disciplinary perspective to develop an analytical framework. Furthermore, we calibrate this analytical framework to multiple mini case studies by reviewing previous IS publications that use multiple mini case studies to provide guidelines to conduct multiple mini case studies rigorously. We also offer a conceptual definition of multiple mini case studies, distinguish them from other research approaches, and position multiple mini case studies as a pragmatic and rigorous approach to research emerging and innovative phenomena in IS.
Keywords: 330; Case study research; Multiple mini case study; Short case study; Methodological guidance